The Effect of Implementing PSAK 72 in Recognizing Business Income from Outsourcing Labor Provision Services and Reconciling Income Tax Returns and VAT (Case Study at PT XYZ) - Payaw, Daniel; Nugrahanti, Trinandari P (Eastasouth Institute, 2024)
The demands of globalization have led to increased cross-border transactions, necessitating the harmonization of financial reporting standards. PSAK 72, adopted from IFRS 15, was implemented in Indonesia on January 1, 2020, impacting various sectors, including the outsourced labor provision services sector. This study focuses on PT XYZ, examining the significant effects of PSAK 72 on income recognition and cost reporting, compared to the previous PSAK 23. The implementation of PSAK 72 resulted in a substantial increase in reported income and costs, despite minimal growth in customer numbers and contracts. The study also explores the fiscal adjustments required to reconcile income reporting between commercial financial reports and tax returns, highlighting the differences in income recognition principles between PSAK 72, the Income Tax Law, and VAT regulations. Through qualitative case study methods, including interviews, document analysis, and literature review, the research provides insights into the impact of PSAK 72 on financial reporting and tax compliance for entities in the outsourced labor services sector. The findings suggest the need for entities to adopt proper recording practices and for tax authorities to update regulations in line with evolving accounting standards to ensure legal certainty and minimize disputes.